An Attempt to Improve Stance Mechanics of Trans-Tibial Amputee Gait by the Design of a Modular Ankle Joint Prosthetic - During, Alastair B (Department of Human Biology, 2019)
Background: A-priori research shows that trans-tibial (TT) amputees display poor gait parameters when walking with low-cost ankle-foot prosthetics (here referred to as baseline AFP’s). This has drastic implications for the amputee populations in the developing world specifically, as they have limited access to advanced prosthetic technologies. Low-cost AFP’s are unable to adequately replicate natural stance mechanics, and reliance on these devices results in increased energy expenditure, osteoarthritis and lower-limb joint deterioration.